User acceptance of online system: a study of banking and airline sector. (1st January 2014) - Khan, Humera; Dominic, P.D.D.
The use of online systems is emerging very rapidly in developing countries. Internet technology becomes the vital part of every business. This study aims to investigate the acceptance rate of an online system by the user to make their transactions online through the internet. This study is based on technology acceptance model (TAM) and proposed a new model for the online system acceptance. The perceived ease of time is a new additive variable in the existing TAM. The research design was based on a survey approach with a sample of 252 users from airline and banking sectors of Pakistan. A questionnaire was administered to collect data from various banks and airlines. The results of this study revealed that perceived ease of time and all independent variables have the significant effect on user acceptance of an online system.